catena-Poly[cobalt(II)-bis(μ-3,7-dichloroquinoline-8-carboxylato-κ(3) N,O:O′)] - Li, Zequan (International Union of Crystallography, 2007)
In the crystal structure of the title compound, [Co(C(10)H(4)Cl(2)NO(2))(2)](n), the Co(II) cation lies on a twofold rotation axis. Each cation is N,O-chelated by the carboxylate anions of two 3,7-dichloroquinoline-8-carboxylate ligands. The second carboxylate O atom of each ligand coordinates to the Co(II) cation of an adjacent molecule, linking the cations into a linear chain. Strong interchain π–π stacking interactions are observed in the crystal structure (perpendicular distance 3.42 Å, centroid-to-centroid distance 3.874 Å)